Making reconciliation work: the role of parliaments: Handbook for parliamentarians n°10 - Mr. Mark Freeman (2005)
The Handbook seeks to provide some responses to this question. It does so by setting out the moral, legal and political dilemmas most commonly associated with democratic and post-confl ict transitions, by exploring the meaning of reconciliation and by highlighting the use of transitional justice mechanisms. Most importantly, it examines ways in which parliaments can foster reconciliation in their own countries in times of transition, and highlights what other parliaments can do to contribute to reconciliation.